Felipe de Esbarroya’s Latin poem in praise of Francisco López de Villalobos’s Glossa litteralis in primum et secundum Naturalis Historiae libros: study, edition and translation: estudio, edición y traducción (Minerva, 2021)
This paper offers a metrical study, edition, annotated translation, notes, and commentary of the Latin poem by Felipe de Esbarroya, a Cordoban physician of the Spanish Holy Inquisition, in praise of the Glossa litteralis in primum et secundum Naturalis Historiae libros (Alcalá de Henares, Madrid, 1524) by Francisco López de Villalobos. Given that the praise is based on the pioneering work by the personal physician of Emperor Charles V, the study and edition of the poem are preceded by an analysis of the reception of Pliny in Spain prior to 1524.
Keywords: Pliny the Elder; Francisco López de Villalobos; Felipe de Esbarroya; Neo-Latin poetry; edition; Humanism